Synthetic control of Prussian blue derived nano-materials for energy storage and conversion application. (December 2019) - Li, Yiwei; Hu, Jiangtao; Yang, Kai; Cao, Bo; Li, Zhibo; Yang, Luyi; Pan, Feng
Abstract: As a presentative material of metal-organic frameworks (MOFs), Prussian blue (PB) draws great attention due to its low cost, facile preparation processes and hollow framework structure. Previous studies show that the PB-derived nanomaterials can inherit part of their features, exhibiting large surface area, inter-connected pores and hierarchical pore sizes, which may promote charge transfer when utilized in energy storage and conversion system. By tuning synthesis conditions (e.g. temperature and atmosphere), nano-materials with desirable structures and properties can be obtained, leading to various usage areas for energy storage and conversion applications (e.g. batteries, supercapacitors and catalysts). In this work, for the first time, various products obtained under different preparation conditions and their applications are summarized in detail in order to offer guiding significance for synthesizing nanoporous materials with special purposes. Highlights: For the first time, the synthetic control of Prussian blue derived nano-materials is symmetrically summarized. Final products are categorized based on their annealing atmospheres. The applications of different materials are reviewed in detail according to their properties. Perspectives on future exploration of new materials with desirable properties are proposed.